PENGARUH STANDAR OPERASIONAL PROSEDUR RETURN BARANG TERHADAP LOYALITAS PELANGGAN DI JNE CABANG GUNUNGSITOLI - Halawa, Lidia Warisani; Gea, Jeliswan B.I.J; Harefa, Idarni; Waruwu, Meiman H. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This study aims to explore the effect of Standard Operating Procedures (SOP) for returning goods on customer loyalty at JNE Gunungsitoli Branch. The research method used is a combination of qualitative and quantitative, with a qualitative approach to understand customer perceptions and a quantitative approach to statistically measure the impact of certain factors. The research location is at JNE Gunungsitoli Branch, North Sumatra, with a research period of six months from April to September 2023. The results of data analysis using SPSS 25 show that SOP return goods have a positive and significant influence on customer loyalty (Significance = 0.000 <0.05). In addition, the coefficient of determination (R-Square) of 0.850 indicates that the SOP for returning goods as a whole affects customer loyalty by 85%, while the remaining 15% is influenced by other factors. Based on the results of the study, it is recommended that companies involved in delivery and return of goods implement a good return goods SOP to increase customer loyalty and gain other positive benefits. Field observations show that good service in the implementation of the return goods SOP can make customers feel satisfied and remain loyal to use the company's services.